The Correctional Services Canada Institutional Mother Child Program: A Look at the Numbers - Paynter, Martha (The prison journal, 2022)
Women are the fastest growing population in federal prison in Canada. Women's incarceration has significant implications for families, as approximately two-thirds have children who face intergenerational trauma, risk of criminalization, and health concerns. The Correctional Services Canada Mother Child Program allows children up to age six to live with their incarcerated mothers. Publicly available information about outcomes associated with the program is scarce, including the number of participants. Using data from 2000–2020 acquired through an Access to Information and Privacy request, this article presents descriptive statistics about the program. Findings indicate the program is underused, and associated outcomes are under-researched.